(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Graphene oxide (GO) has emerged as a promising nanomaterial for enhancing the properties of food and beverage packaging. Its unique physical, chemical, and mechanical characteristics, including high surface area, excellent barrier properties, antimicrobial activity, and mechanical strength, make it an ideal candidate for improving packaging performance. This abstract explores the applications of graphene oxide in food and beverage packaging, focusing on its role in extending shelf life, enhancing food safety, and reducing environmental impact. Incorporating GO into packaging materials improves their barrier properties against oxygen, moisture, and UV radiation, which are critical factors in preserving product freshness. Additionally, the antimicrobial properties of GO help inhibit the growth of foodborne pathogens, reducing the risk of contamination. Furthermore, graphene oxide-based packaging materials can be engineered to be biodegradable and recyclable, addressing environmental concerns associated with conventional plastic packaging. This abstract also discusses potential challenges, such as regulatory issues, cost implications, and safety considerations, associated with integrating graphene oxide in commercial packaging applications. Overall, the incorporation of graphene oxide in food and beverage packaging holds significant promise for creating safer, more sustainable, and higher-performing packaging solutions.